Radiocarbon Content of Dissolved Organic Carbon in the South Indian Ocean. Issue 2 (24th January 2018) - Bercovici, S. K.; McNichol, A. P.; Xu, L.; Hansell, D. A.
Abstract: We report four profiles of the radiocarbon content of dissolved organic carbon (DOC) spanning the South Indian Ocean (SIO), ranging from the Polar Front (56°S) to the subtropics (29°S). Surface waters held mean DOC Δ 14 C values of −426 ± 6‰ (~4, 400  14 C years) at the Polar Front and DOC Δ 14 C values of −252 ± 22‰ (~2, 000  14 C years) in the subtropics. At depth, Circumpolar Deep Waters held DOC Δ 14 C values of −491 ± 13‰ (~5, 400 years), while values in Indian Deep Water were more depleted, holding DOC Δ 14 C values of −503 ± 8‰ (~5, 600  14 C years). High‐salinity North Atlantic Deep Water intruding into the deep SIO had a distinctly less depleted DOC Δ 14 C value of −481 ± 8‰ (~5, 100  14 C years). We use multiple linear regression to assess the dynamics of DOC Δ 14 C values in the deep Indian Ocean, finding that their distribution is characteristic of water masses in that region. Key Points: 14 C ages of DOC in the South Indian Ocean range from 2, 000 to 4, 400  14 C years at the surface and reach ~5, 600  14 C years at depth There are distinct 14 C signatures of DOC in the deep Indian Ocean's water masses DOC 14 C gradients in deep waters are consistent with their respective placement in overturning circulation